A High Frequency, High Efficiency, High Power Factor Isolated On-board Battery Charger for Electric Vehicles - (:unkn) unknown (My University, 2018)
In this paper, a high frequency, high efficiency and high power factor isolated on-board battery charger is proposed. The proposed topology includes two parts, AC/DC power factor correction (PFC) circuit unit and DC/DC converter unit. For the PFC circuit, SiC based totem-pole interleaved bridgeless PFC is selected, the diode bridge rectifier is eliminated. In addition, it can operate in continuous conduction mode (CCM) thanks to the low reverse recovery losses of the SiC MOSFETs. Besides, the interleaved technology minimizes the input current ripple. The DC/DC converter unit is composed of two LLC resonant converters sharing the same full-bridge inverter with constant switching frequency. The outputs of two LLC resonant converters are connected in series. One of the LLC resonant converter is operating at the resonant frequency, which is the highest efficiency operation point; while magnetic control is adopted for the second LLC resonant converter to fulfill the duty of providing closed-loop control for constant voltage (CV) and constant current (CC) charge modes. The proposed topology can achieve zero voltage switching (ZVS) for all primary switches and zero current switching (ZCS) for all secondary diodes during both CC and CV modes. Furthermore, the constant switching frequency is simplified the electromagnetic interference (EMI) filter design. Simulation studies for 3.3kW power level and 100kHz switching frequency are performed, the simulation results are presented to verify the feasibility and validity of the proposed topology.
Keywords: electric vehicles; high efficiency; high frequency; high power factor; magnetic control; on-board battery charger